THE CINDERELLA COMPLEX, ADVERSE CHILDHOOD EXPERIENCES, AND THE MEANING AND PURPOSE OF LIFE IN WOMEN: A WEB-BASED CROSS-SECTIONAL STUDY - Özçalık, Habibe Bay; Ataş, Ayşe Nur; Yılmaz, Sema Dereli (International Journal of Child, Youth and Family Studies, 2024)
This study aimed to investigate the correlations between the Cinderella complex — the desire in a woman sto be cared for and protected by another person, particularly a man — and each of two factors: adverse childhood experiences (ACEs) and the meaning and purpose of life. Designed as web-based cross-sectional research, the study was conducted from March 2022 to June 2022. The data were collected via social media platforms, with 356 women participating. The instruments used were a personal information form, the Cinderella Complex Scale, the Turkish ACE-TR questionnaire, and the Meaning and Purpose of Life Scale. Means of scores obtained by participant women from the Cinderella Complex Scale, the ACE-TR questionnaire, and the Meaning and Purpose of Life Scale were successively 66.37±22.77, 1.28±1.71, and 65.13±10.35 points. Women's average scores on the Cinderella Complex Scale and ACE-TR Scale were low, and their average scores on the Meaning and Purpose of Life Scale were high. Participants’ descriptive characteristics — education level, employment status, spouse’s education level, and family type — affected their Cinderella Complex Scale scores, while their ACE-TR scores had no statistically significant effect. There is a significant relationship between scores on the Cinderella Complex Scale and scores on the Meaning and Purpose of Life Scale. To avoid developing a Cinderella complex, it is recommended that women adopt a wider perspective on life, continually upgrade their skills, become more independent in their thoughts and actions, and create a personal space where they can spend quality time in order to find more meaning in life.